Pengaruh Pemberian Informasi terhadap Tingkat Pengetahuan Swamedikasi Diare kepada Warga Desa Nguter RT 01 RW 07 - SM, Ahmad Fatih Amin; Indrasari, Tika; Rejeki, Sri; Parmadi, Anom (Indonesian Journal on Medical Science, 2024)
Diarrhea is a disease that is often found in society. Diarrheal disease is mainly caused by contaminated food and drink due to poor access to hygiene. Diarrhea is a dangerous disease because it can cause death and can cause extraordinary events (KLB). The main cause of death in diarrhea is dehydration, namely loss of fluids and electrolyte salts in diarrheal stools. Diarrheal disease or often referred to as gastroenteritis is a public problem in Indonesia. Diarrhea is a disease characterized by an increase in the frequency of defecation more than usual, more than 3 times/day, accompanied by a consistent change in stool (to become liquid) with or without blood or mucus. This study aims to determine the effect of providing information on the level of knowledge of residents about diarrhea self-medication in Nguter Village, Nguter District, Sukoharjo Regency. This research is a type of quantitative analytic observational research. The approach used in this research design is a "pre-experimental design". This research is intended to increase the knowledge of the Nguter Village residents through a learning process to increase the cognitive knowledge of the Nguter Village residents through a learning approach by giving leaflets. The results of this study found that the significance value was (p) = 0.000 <0.05. Providing information has a positive effect on the level of knowledge of diarrhea self-medication in residents of Nguter Village RT 01 RW07.